Synchrophasor Simulation With Virtual PMUs in Power System for Off-Line Studies - Arias Atiaja, Fernando Rafael (2025)
One of the main components that make up the wide area monitoring system (WAMs) are the Phasor Measurement Units (PMUs), devices that allow dynamic analysis of the state of the electrical system, these devices allow phasor estimation representing the magnitudes of voltage and current angles and guaranteeing by means of time synchronization and sampling frequency to visualize the system in real time and compare phasors measured at different points of the network. This study presents a dynamic monitoring platform with PMUs for a two-area power system, the approach starts with the development and verification of a reference model example 12.6 (P. Kundur, Power system stability and control), simulated in DIgSILENT PowerFactory software, then a dynamic study is performed by implementing disturbance events in order to extract data of voltages and currents in magnitude and angle, in addition, an algorithm is implemented using Python software that serves as a virtual PMU for reading and sending data recorded through a fictitious ip network that will be extracted by the Pyscript software for viewing and use of data for monitoring, also shows the dynamic monitoring synchrophasor by PMU Connection Tester software that communicates through the virtual ip sent from Python, as a result the response graph is obtained by displaying angles of virtual PMUs.